“Finishing One Big Adventure in Order to Embark on Another”: Exploring University Research Blogs - Tomášková, Renáta (Research in Language, 2019)
The article focuses on blogs related to research activities of the academic community. Research-related blogs as components of university websites have developed into an array of sub-genres shaped by specific foci, their authors and the desired audiences. The data set consists of fifty posts from ten blogs of six universities. Drawing upon Swales’ methodology of genre analysis, the study explores the generic structure of the blog posts, reveals the communicative purposes they can fulfil within the landscape of university websites, identifies significant communication strategies, and explores the roles the blogs may serve in communicating science to the diverse audiences they potentially address. The analysis has shown that the blogs help accomplish the general goals of informing about the university and promoting it providing a personalized view and engaging the reader, manifest loose but recurrent generic structuring, and can be vehicles of knowledge dissemination as well as knowledge construction.